2020
DOI: 10.1088/1361-6560/ab857b
|View full text |Cite
|
Sign up to set email alerts
|

Investigating conditional GAN performance with different generator architectures, an ensemble model, and different MR scanners for MR-sCT conversion

Abstract: Recent developments in magnetic resonance (MR) to synthetic computed tomography (sCT) conversion have shown that treatment planning is possible without an initial planning CT. Promising conversion results have been demonstrated recently using conditional generative adversarial networks (cGANs). However, the performance is generally only tested on images from one MR scanner, which neglects the potential of neural networks to find general high-level abstract features. In this study, we explored the generalizabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…To date, four scientific studies have already investigated the performance of DL‐based sCT in a multicenter setting 71,114–116 . These studies have been reported only for MR‐only RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, four scientific studies have already investigated the performance of DL‐based sCT in a multicenter setting 71,114–116 . These studies have been reported only for MR‐only RT.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed examination of different 2D-paired GANs against U-net with different loss functions by Largent et al 113 showed that U-net and GANs could achieve similar image-and dose-base performances. Fetty et al 115 focused on comparing different generators of a 2D-paired GAN against the performance of an ensemble of models, finding that the ensemble was overall better than single models being more robust to generalization on data from different scanners/centers. When considering CNNs architectures, it is worth mentioning using 2.5D-dilated CNNs by Dinkla et al, 102 where the m2D training was claimed to increase the robustness of inference in a 2D+ manner, maintaining a big receptive field and a low number of weights.…”
Section: Mr-only Radiotherapymentioning
confidence: 99%
“…This being said, the relationship between the amplitude of the sCT error and the subsequent error inaccuracies in PET attenuation correction and radiation therapy dose planning is not predictable. This was previously studied by Fetty et al who found no correlation between MAPE and the radiation therapy dosimetric plan evaluation [ 35 ]. Under this perspective, we focused the validation of our study on HU accuracy and the convenience of our method in the context of the usual diagnostic and therapeutic workflow in gynecological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…As for the hyperparameter λ , an initial analysis of its effect had already been initiated by Isola et al . [ 31 ], and was subsequently adopted by different researchers in the medical imaging field [ 35 ], [ 37 ], [ 38 ]in which the choice of λ = 100 yielded the best results. In line with the previously published literature [ 31 ], [ 37 ], [ 38 ], we chose λ = 100 in the U-cGAN and sU-cGAN loss functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation